Chiari malformation clusters describe differing presence of concurrent anomalies based on Chiari type. (December 2018) - Horn, Samantha R.; Shepard, Nicholas; Vasquez-Montes, Dennis; Bortz, Cole A.; Segreto, Frank A.; De La Garza Ramos, Rafael; Goodwin, C. Rory; Passias, Peter G.
Highlights: A large proportion of patients with Chiari malformation have at least one concurrent anomaly. Common neurologic associations include tethered cord, syringomyelia and hydrocephalus. Additional body systems are often involved with worsening hind brain defects. Abstract: Chiari malformations are structural defects in the posterior fossa where the cerebellum displaces caudally into the foramen magnum and upper spinal canal. These malformations are classified by severity as Types 1–4, each presenting with different associated and/or concurrent conditions and anomalies. The aim of this study was to utilize a nationwide database to study patients with Chiari malformations including their concurrent diagnoses and associated anomalies. Using a retrospective review of the Nationwide Inpatient Sample (NIS) database from 2003 to 2012, Chiari malformations were assessed by Chiari type and rates of concurrence for various additional anomalies were evaluated using cross-tabulations. There were 305, 726 national cases of Chiari Type 1, 119, 632 cases of Chiari Type 2, 15, 540 cases of Type 3, and 79, 663 cases of Type 4. Overall 44.3% of Chiari patients have at least one concurrent anomaly. Stratified by Chiari Type, 7.1% of Type 1 patients, 12.3% of Type 2, and 100% of Type 3 and 4 have at least one concurrent anomaly. The most common isolated neurologic associations were tethered cord, syringomyelia, and hydrocephalus, while the most common anomaly clusters were syringomyelia and scoliosis in Type 1 (0.63), tethered cord syndrome and scoliosis (0.72%) in Type 2, encephalocele and acquired hydrocephalus (11.45%) in Type 3, and reduction deformity of the brain with acquired hydrocephalus (15.95%) in Type 4. Chiari malformations have strong associations with other abnormalities outside of known relationships in the current classification. While neurologic abnormalities are most common, additional body systems are frequently involved especially with worsening hindbrain defects.